2018
DOI: 10.1038/s41598-018-33506-8
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis of the genes regulating phytohormone and cellular patterning in Lagerstroemia plant architecture

Abstract: Plant architecture is a popular research topic because plants with different growth habits that may generate economic or ornamental value are in great demand by orchards and nurseries. However, the molecular basis of the architecture of woody perennial plants is poorly understood due to the complexity of the phenotypic and regulatory relationships. Here, transcriptional profiling of dwarf and non-dwarf crapemyrtles was performed, and potential target genes were identified based on the phenotype, histology and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 68 publications
1
19
0
Order By: Relevance
“…Longer internodes usually associated with trailing type while upright types had shorter internodes. In this set of genes, the carbohydrate metabolic processes and their regulation were enriched, consistent with the report on internode length in Lagerstroemia 18 . A total of 709 of these transcripts (unigenes) were annotated with the KO (Kyoto Encyclopedia of Genes and Genome (KEGG) Ortholog) database, and the most representative pathways were “Metabolic pathways” (98), “Biosynthesis of secondary metabolites” (44), and “RNA transport” (21) (Supplementary Table 5 ).…”
Section: Resultssupporting
confidence: 90%
“…Longer internodes usually associated with trailing type while upright types had shorter internodes. In this set of genes, the carbohydrate metabolic processes and their regulation were enriched, consistent with the report on internode length in Lagerstroemia 18 . A total of 709 of these transcripts (unigenes) were annotated with the KO (Kyoto Encyclopedia of Genes and Genome (KEGG) Ortholog) database, and the most representative pathways were “Metabolic pathways” (98), “Biosynthesis of secondary metabolites” (44), and “RNA transport” (21) (Supplementary Table 5 ).…”
Section: Resultssupporting
confidence: 90%
“…Lagerstroemia, which exhibits various plant architectures, has a large number of flowers and a long flowering period. Moreover, most of its seedlings with short juvenile periods grow rapidly, as do flowers with an age of over 1 year 32 . Therefore, Lagerstroemia is widely used in gardens and has specific economic benefits 33 .…”
Section: Introductionmentioning
confidence: 99%
“…Two markers that are highly correlated with internode length and one marker that is highly correlated with primary lateral branch height have been validated in crape myrtle 34 . The analysis of transcriptome and hormone levels in dwarf and non-dwarf crape myrtles suggested that internode length is controlled by an interaction between auxin and GA4 32 . The weeping plants examined in our study are dwarf plants with weeping branches.…”
Section: Introductionmentioning
confidence: 99%
“…Based on all the highly polymorphic primers in crape myrtle, two near-isogenic pools (B Z , B P ) and three standard and three creeping individuals were then randomly selected and screened by SSRs. The 322 pairs of primers used in the experiment were developed using the transcriptome data from a previous study [45] (Table S1).…”
Section: Screening Ssr Markers Linked To Creeping Strainsmentioning
confidence: 99%